Comparison of Bupivacaine and 2-Chloroprocaine with and without Fentanyl for Subarachnoid Block in Inguinal Hernia Repair Surgery: A Randomised Controlled Study - Avani Tiwari (JCDR Research and Publications Private Limited, 2021)
Introduction: Providing an adequate intraoperative anaesthesia with a prolonged pain-free interval is the prime priority of an anaesthesiologist. Since the decline in use of 2-chloroprocaine in 1956, due to side-effects of its preservative sodium bisulfite, the preservative free drug has recently witnessed a comeback in clinical practice. Aim: To compare the efficacy of bupivacaine and 2-chloroprocaine with and without fentanyl in subarachnoid block for inguinal hernia repair surgery. Materials and Methods: This randomised controlled study was carried out on 102 male patients of 18-65 years of age, American Society of Anesthesiologists (ASA) grade I or II, scheduled for inguinal hernia repair. The study was conducted from May 2019 to November 2020. The patients were randomly divided into three groups of 34 each. In group A, the subarachnoid block was administered with injection 0.5% bupivacaine (H) 10.5 mg. In group B, patients were administered, injection 2-chloroprocaine 40 mg diluted with 0.5 mL of saline. In group C, the patients were administered with injection 2-chloroprocaine 40 mg with 25 µg of injection fentanyl (0.5 mL). The adequacy of intraoperative anaesthesia in terms of onset and duration of sensory and motor blockade, haemodynamic parameters, postoperative urinary retention and other side-effects were evaluated. The parameters were compared using Analysis of variance test (>2 groups). If statistically significant difference was found in ANOVA, appropriate post-hoc (LSD/Bonferroni) was used to assess statistical significance of pair-wise comparisons. Results: The mean time of onset of the motor and sensory block was faster in group B (3.57±0.66, 2.68±0.58 min), by almost 1 minute than in the bupivacaine and fentanyl group (4.57±0.79, 3.59±0.61 min) (4.99±1.01, 4.04±0.99 min) respectively. The mean difference was statistically significant (p-value <0.05). The mean duration of the motor and sensory blocks between the groups revealed statistically significant difference between groups A and B as well as groups A and C. However, between groups B and C, there was no significant difference as far as motor block duration is concerned. Group B had significantly shorter duration of the motor and sensory block amongst the three groups. Conclusion: Addition of intrathecal fentanyl significantly prolonged the onset and duration of sensory and motor block, with minimally extending the time to complete recovery.